Penerapan Pembelajaran Tutor Sebaya Dengan Strategi Everyone is a Teacher ( ETH ) Pada Praktek Pembelajaran Tematik SD Di Program Studi PGSD IKIP PGRI Semarang - Fine Reffiane; Djariyo Djariyo (Universitas PGRI Semarang, 2011)
AbstrakThematic learning is learning that is designed based on certain themes. In his discussion themes were reviewed from a variety of subjects. Thematic learning provides the breadth and depth of curriculum implementation, offering vast opportunities for students to bring up the dynamics in education. In cycle I obtained an average yield of 81.5% active students, the average ability of students 57.7%, an average of 7.4 and active learning in peer tutoring and learning activities to teach the average value of 7, 56. In cycle II, obtained an average yield of 83.4% active students, the average ability of students 73.4%, the average learning outcomes 8.8 and the average value of active peer tutors in the teaching-learning 7.75.Keywords: ETH, Peer Tutor